THE IMPACT OF THE DINES MODEL AS AN EDUCATIONAL MEDIATOR ON COGNITIVE ACHIEVEMENT AND LEARNING OVERHEAD PASSING SKILL IN VOLLEYBALL - Hameed Hammad Khalaf; Abrahim Ali Abrahim; Noor Majid Khaleel; Jasim Nafi Hummadi; Ameer Jaber Mushref; Othman Adham Ali (Proximus Journal Publishing, 2024)
The research targets the development and application of educational modules that follow the Dines model for demonstration and also to teach the overhead ball passing technique in volleyball among middle school students in order to improve their cognitive performances. The experimental research, including control and experimental groups, was formed by using pre- and post-tests administered throughout a three-week period, which involved 30 male students enrolled at Al-Zaytoun Model School for Boys. The educational program was organized utilizing different learning formats, which encompassed poster displays, data presentations, and in-depth explanations of motor performance concepts complemented with themed cognitive inquiries. The curriculum design was the development of a series of exercises, from easy tasks to more complex ones, with periodic corrections and feedback provided to the students. Post-assessment evaluation disclosed some notable improvements in problem-solving skills and cognitive abilities among conveners. The gradual and incremental approach provided by the curriculum allowed for higher student engagement and understanding of the technique. Integrating the cognitive, historical, mental, motor, technical, and legal elements while teaching overhead passing strategy enhances students' understanding, encouraging inclusive skill acquisition and cognitive development.
Keywords: Dines model; instructional mediator; cognitive achievement